EXPLORANDO AS POTENCIALIDADES DOS SENTIDOS NA PESQUISA EM EDUCAÇÃO MATEMÁTICA: EXPERIMENTAÇÕES SENSORIAIS COM PROFESSORES DE MATEMÁTICA EM FORMAÇÃO - ASAPH ORTOLANI BEDOIA (2024)
This present study aims to problematize how senses can contribute to the production of interviews with mathematics teachers in training, within a Mathematics Education research inspired by Oral History methodology. The research questions the ways in which science has shaped the constitution of knowledge, disregarding knowledge derived from sensory experience. Dialogue with various authors and theories aims to understand the use of senses and their potential in knowledge formation. Experimentations were conducted with four mathematics teachers in training, involving the five senses: Vision, Hearing, Touch, Smell, and Taste, all present in the teaching reality. In addition to the experimentations, other procedures were carried out, such as conversations prompted by the experiments, the production of a poster, and the creation of a "room of senses" through drawings, collages, and figures. Besides these records, the experimentations were recorded and photographed. To present these materials, we turned to Transmedia Narratives, thus materializing the experience through different media outlets. When we engage the senses, interviewees narrate beyond mere facts, bringing forth feelings linked to memories, which highlights how potent their use can be in research. The senses evoked more than what was expected and provided alternative understandings regarding their use in research in the field of Mathematics Education.